2020
DOI: 10.1108/scm-01-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

The blockchain-based Halal traceability systems: a hype or reality?

Abstract: Purpose Given the emerging nature of integrating blockchain into food traceability systems, this study aims to investigate the intention to participate in a blockchain-based Halal traceability system through a united model that consists of Halal orientation strategy, institutional theory and diffusion of innovation theory. Design/methodology/approach A sample that consists of 143 Malaysian Halal food and beverage manufacturers was drawn from Halal Malaysia Official Portal using the simple random sampling tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 91 publications
2
77
0
5
Order By: Relevance
“…The same was found for the influence of relative advantage on intention to use [89,90]. Compatibility was found to influence perceived usefulness of DLT [91][92][93], perceived ease of use [75,94], and intention to use and supported by previous studies [45,76,95]. Finally, perceived ease of use showed a significant influence on perceived usefulness during the DLT adoption [84,96,97].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The same was found for the influence of relative advantage on intention to use [89,90]. Compatibility was found to influence perceived usefulness of DLT [91][92][93], perceived ease of use [75,94], and intention to use and supported by previous studies [45,76,95]. Finally, perceived ease of use showed a significant influence on perceived usefulness during the DLT adoption [84,96,97].…”
Section: Resultssupporting
confidence: 80%
“…Our review of previous studies indicated that while consumers may experience higher relative benefits, they may also perceive the technology to be of higher utility. Previous findings (e.g., [28,45,46]…”
Section: Relative Advantagementioning
confidence: 88%
“…Thus, the need for proper guideline on halal supply chain management for producers is undeniable (Shafii & Wan Siti Khadijah, 2012). It is reasonable for producers with a level of halal awareness to apply the latest technology in halal traceability, such as blockchain (Hew, Wong, Tan, Ooi, & Lin, 2020). According to Rashid, Supian, and Bojei (2018), halal traceability can influence the halal integrity of the halal supply chain, which is a key element of halal supply chain performance.…”
Section: Discussionmentioning
confidence: 99%
“…This is a meaningful improvement in managing food quality and safety, especially for product lines in which different grades and types of food can be easily mixed, such as processed meat (Pearson et al 2019) or soybean (Salah et al 2019). Halal food is another example where increased transparency is hugely beneficial (Hew et al 2020). Furthermore, businesses can rely on Blockchain to obtain reliable information about food provenance and communicate such information to consumers to gain a competitive edge over others in the market (Helo and Hao 2019;Montecchi, Plangger, and Etter 2019;Caldarelli, Rossignoli, and Zardini 2020).…”
Section: Enhance Food Chain Transparencymentioning
confidence: 99%